Derivation of Transcranial Doppler Criteria for Angiographically Proven Middle Cerebral Artery Vasospasm after Aneurysmal Subarachnoid Hemorrhage. Issue 4 (19th November 2012) - Sebastian, Joseph; Derksen, Carol; Khan, Khurshid; Ibrahim, Mohammad; Hameed, Bilal; Siddiqui, Muzaffar; Chow, Michael; Findlay, J. Max; Shuaib, Ashfaq; Saqqur, Maher
ABSTRACT BACKGROUND Transcranial Doppler (TCD) has been subjected to criticism for detecting vasospasm (VSP). Our study's aim is to derive criteria for middle cerebral artery (MCA) vasospasm (MCA‐VSP) based on cerebral angiography (CA). METHODS A prospective data of patients with aneurysmal subarachnoid hemorrhage (aSAH) from January 2004 to August 2009. TCD was performed daily from day 2 to 14 from symptom's onset. Follow‐up CA was done at day 7‐9. TCD mean flow velocities (MFV) of all vessels at baseline (b), middle (m) and before CA (preangio) were recorded. Several MCA MFV ratios were computed. Moderate to severe VSP on CA was defined as >1/3 luminal narrowing. Univariate and stepwise logistic regression analysis were performed. RESULTS One hundred sixty‐nine patients (338 MCA) with aSAH were included, mean age: 54.8 ± 13, women: 103 (62%). Twenty‐nine patients (8.6%) had angiographic MCA‐VSP. TCD scoring system of 3 points for MCA‐VSP was computed based on (a) bMCA MFV ≥ 120 cm/s (sensitivity: 59.3%, specificity: 85%, PPV: 36.4%, NPV: 93.5%, P < .001) (1 point), Preangio MCA MFV ≥ 150 cm/s (79.3%, 89.9%, 39%, 97.3%, <.001) (1 point), and affected preangio MCA/bMCA MFV ratio ≥1.5 (84%, 63%, 25.6%, 96.3%, .001) (1 point). The score of 3 has 96% sensitivity and 96% specificity (OR: 300) whereas the score of 1 has 12% sensitivity and 58% specificity (OR: 4.3) for identifying MCA‐VSP. CONCLUSION TCD stringent criteria for moderate to severe MCA‐VSP are feasible and applicable in aSAH population.